A Simple Technique For Estimation Of Reservoir Permeability From Seismic Reflection Data Based On Biot's Teorem - Sismanto, . (2010)
Relationships among elastic parameters and rock properties, and ultimate reservoir parameters have been established in continuum mechanics and rock physics. Therefore, it should be possible to estimate reservoir permeability from the seismic data. We used Bioi's solution of wave equation in an elastic porous medium and the approximations ofTurgut Yamamoto to allow an establishment of a linear relationship between attenuation coefficient or amplitude ratio as a function of the inverse of the square of frequency. The slope of this function includes the permeability. It can be shown that this technique agrees to the measurement of the permeability of a porous medium from seismic waveforms. We examined this technique to estimate the reservoir permeability by using synthetic seismogram data. The result show that has an error less than 5 %, it means that the study of permeability estimation from surface seismic data is possible by using an accurate calibration step. The procedure is tested on 3D seismic data over part of Duri field in central Sumatra, Indonesia. The simplicity of the theoretical approach requires the introduction of an empirical calibration factor that is provided by well SM#A in the area. This factor is then implemented to estimate the permeability with seismic data on the field; it gives a permeability map of the study area. A key result of the study is that permeability estimation with surface seismic data are possible but requires calibration. A confirmation and validation of this procedure will be subject to future work.